Highly Efficient Recyclable Sol Gel Polymer Catalyzed One Pot Difunctionalization of Alkynes - Justin Domena; Carlos Chong; Qiaxian R. Johnson; Bhanu P. S. Chauhan; Yalan Xing (Molecules, 2018)
Amino-bridged gel polymer P1 was discovered to catalyze alkyne halo-functionalization in excellent yields, regioselectivity, functional group compatibility, and recyclability. We have observed that both aromatic and aliphatic alkynes can be converted to α,α-dihalogenated ketones in the presence of polymer P1 under metal-free conditions at room temperature within a short reaction time.